2022
DOI: 10.5530/ijper.56.4.170
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Appropriate use of Niosomes for the Treatment of Skin Cancer

Abstract: Both melanoma and non-melanoma are the most common types of skin cancers affecting various populations across the globe. Skin malignancy is more prevalent among Caucasian populations. Non-melanoma types of skin cancers are further classified as basal cell and squamous cell carcinomas, respectively. The incidence of non-melanoma type of cancers is relatively higher than melanoma type of skin cancers. Recently published data shows that melanoma of the skin stands as the seventeenth most common type of cancer acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Its key features are the increased permeability of niosomes through the SC and the ability to reach the desired site of action [127]. Both hydrophilic and lipophilic drugs can be added to vesicular systems containing nonionic surfactants without causing toxicity.…”
Section: Niosomes Liposomesmentioning
confidence: 99%
“…Its key features are the increased permeability of niosomes through the SC and the ability to reach the desired site of action [127]. Both hydrophilic and lipophilic drugs can be added to vesicular systems containing nonionic surfactants without causing toxicity.…”
Section: Niosomes Liposomesmentioning
confidence: 99%
“…On the other hand, non-ionic surfactant-containing niosomal vesicular systems could be a different type of carrier system for transdermal drug administration [ 10 ]. These systems have several advantages over liposomal systems, including versatility, great penetration potential, excellent physical and chemical stability, lower production cost, reduced toxicity, ease to be formulated and scale-up, biocompatibility, biodegradability, and non-immunogenicity [ 11 , 12 ]. Several studies have demonstrated the ability of niosomes to transport drug molecules through intact skin, indicating the potential of this carrier in transdermal therapy [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%